2017
DOI: 10.5194/os-2017-84
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics of high monsoon wind-waves observed at multiple stations in the eastern Arabian Sea

Abstract: Abstract. The growth and decay of surface wind-waves during one-month period in a typical Indian summer monsoon is investigated based on the data collected at 9 to 15 m water depth at 4 locations in the nearshore waters of the eastern Arabian Sea covering a spatial distance of ~350 km. The significant wave height varied from 0.7 to 5.5 m during the data collection considered in the analysis. The heights of waves during the measurement period often exceed 3 m. The most extreme wave 10 height is 1.50 to 1.62 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The H max / H s ratio in the study area varies from 1.46 to 2.3 with an average value of 1.87 during 1979–2017. Amrutha and Sanil Kumar () observed that in the coastal waters of the eastern Arabian Sea, the H max / H s ratio is 1.50–1.62 times the H s for different locations.…”
Section: Resultsmentioning
confidence: 99%
“…The H max / H s ratio in the study area varies from 1.46 to 2.3 with an average value of 1.87 during 1979–2017. Amrutha and Sanil Kumar () observed that in the coastal waters of the eastern Arabian Sea, the H max / H s ratio is 1.50–1.62 times the H s for different locations.…”
Section: Resultsmentioning
confidence: 99%
“…During JJA, the AS is dominated by mixed sea state i. e, a combination of strong monsoon winds forced wind sea and swell 22 , 29 and peak wave period above 15 s is rarely seen in this period indicating non-dominance of SIO swells. A recent study shows that the SIO swell propagation is more towards BOB during JJA 41 .…”
Section: Resultsmentioning
confidence: 99%
“…In the SW monsoon season, the enhanced south‐westerlies in the Indian Ocean strengthen the generated swells. The high waves (SWH ~3 to 5.5 m) in the eastern AS during the SW monsoon are because of the strong cross‐equatorial winds of the Findlater Jet (Findlater, 1969), which produces high waves of 4–6 m in the western AS and propagate to the eastern AS (Amrutha and Sanil Kumar, ). In the study area, SW monsoon wave heights are larger and elevated above 1.5 m during 38.4% of the time.…”
Section: Discussionmentioning
confidence: 99%